The Impact of Sports Demonstration Videos on Students’ Speaking Fluency and Accuracy - Sianipar, Rimma; Sinaga, Andromeda Valentino (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2025)
This study analyzes the impact of creating sports demonstration videos on students' speaking fluency and accuracy in English. The research subjects were first-semester students of the Physical Education, Health, and Recreation Program at Universitas Negeri Makassar. Data were collected through video transcript analysis and student questionnaires. The findings indicate that practicing instructional delivery in videos enhances speaking fluency, as shown by reduced pauses and word repetitions. However, in terms of accuracy, errors were still found in grammar, word choice, and pronunciation of technical sports terms. The primary factors affecting accuracy were the lack of speaking practice in academic contexts and insufficient direct correction. This study confirms that project-based tasks, such as video creation, can be an effective strategy for improving students' speaking skills in second language learning.